A apódexis herodotiana: um modo de dizer o passado - Ribeiro, Tatiana Oliveira (2010)
“This is apodexis histories of Herodotus from Halicarnassus”. This saying, opening Herodotus’ Histories, has transmitted to the western culture not only the word epitomizing the research activity of the Historian, the historie, but also the one denoting how all the large amount of the material the had collected and pondered is organized and exhibited: the apodexis. The present dissertation thematizes this latter concept and observes the nuances it assumes in the course of Herodotus’ work, as well as its relative constancy of signification in other prose texts, mainly epideictic writings. As a result from the relationship of convergence between apode(i)xis and epide(i)xis, the present work suggests to consider the performance perspective of Herodotus’ text, based on textual evidence pointing to the existence of a display practice the circulating in Ancient Greece from 5 century onwards. Herodotus’ apodexis figures as a way of telling time, space, people and their nomoi, and also as a way of reelaborating the narratives from the past and interpretating the present.